Use of gemcitabine, oxaliplatin, and anti‐CD20 therapy in children and adolescents with non‐Hodgkin lymphoma unfit for intensive therapy. Issue 4 (24th January 2023) - Bender, Jonathan D.; Rubinstein, Jeremy D.; Mizukawa, Benjamin; Perentesis, John P.; Pommert, Lauren
Abstract: Multiagent immunochemotherapy affords excellent outcomes in pediatric non‐Hodgkin lymphoma (NHL); however, scarce data exist for patients unfit for intensive treatment. Rituximab, gemcitabine, and oxaliplatin (R‐GemOx) is well tolerated and efficacious in elderly adults with NHL; however, its use has not been described in pediatrics. In this retrospective, single‐center study, six children with mature B‐cell NHL and significant comorbidities received anti‐CD20 therapy with GemOx (rituximab or obinutuzumab or ofatumumab with gemcitabine and oxaliplatin [R/O‐GemOx]). R/O‐GemOx was well tolerated and resulted in complete response in two of three patients with newly diagnosed NHL and one of three patients with primary refractory NHL. R/O‐GemOx is a viable treatment option for children with NHL who cannot tolerate intensive therapy.